An Inducible Microbacterium Prophage vB_MoxS-R1 Represents a Novel Lineage of Siphovirus - Hongrui Zheng; Binbin Liu; Yongle Xu; Zefeng Zhang; Hongcong Man; Jihua Liu; Feng Chen (Viruses, 2022)
Lytic and lysogenic infections are the main strategies used by viruses to interact with microbial hosts. The genetic information of prophages provides insights into the nature of phages and their potential influences on hosts. Here, the siphovirus vB_MoxS-R1 was induced from a Microbacterium strain isolated from an estuarine Synechococcus culture. vB_MoxS-R1 has a high replication capability, with an estimated burst size of 2000 virions per cell. vB_MoxS-R1 represents a novel phage genus-based genomic analysis. Six transcriptional regulator (TR) genes were predicted in the vB_MoxS-R1 genome. Four of these TR genes are involved in stress responses, virulence and amino acid transportation in bacteria, suggesting that they may play roles in regulating the host cell metabolism in response to external environmental changes. A glycerophosphodiester phosphodiesterase gene related to phosphorus acquisition was also identified in the vB_MoxS-R1 genome. The presence of six TR genes and the phosphorus-acquisition gene suggests that prophage vB_MoxS-R1 has the potential to influence survival and adaptation of its host during lysogeny. Possession of four endonuclease genes in the prophage genome suggests that vB_MoxS-R1 is likely involved in DNA recombination or gene conversion and further influences host evolution.